Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1161/circulationaha.110.988915
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle Myosin Light-Chain Kinase Deficiency Attenuates Atherosclerosis in Apolipoprotein E–Deficient Mice via Reduced Endothelial Barrier Dysfunction and Monocyte Migration

Abstract: Background Endothelial dysfunction and monocyte migration are key events in the pathogenesis of atherosclerosis. Non-muscle myosin light-chain kinase (nmMLCK), the predominant MLCK isoform in endothelial cells, has been shown to contribute to vascular inflammation by altering endothelial barrier function. However, its impact on atherogenesis remains unknown. Methods and Results We investigated the role of nmMLCK in the development of atherosclerotic lesions in apolipoprotein E-deficient (apoE−/−) mice fed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 41 publications
3
86
0
Order By: Relevance
“…Src-mediated phosphorylation of b-catenin and/or VE-cadherin has been shown to be an important signaling event leading to adherens junction uncoupling (Cohen et al, 1999;Dejana et al, 2008;McEwen et al, 2012). We recently reported that Src-activation in response to thrombin was dependent on the presence of nmMlck (Sun et al, 2011), suggesting that nmMlck could be upstream of Src-mediated tyrosine phosphorylation of the adherens junction and subsequent uncoupling. However, it is also thought that b-catenin that is dissociated from the adherens junction needs to be phosphorylated at serine residues in order to be stable in the cytoplasm (Daugherty and Gottardi, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Src-mediated phosphorylation of b-catenin and/or VE-cadherin has been shown to be an important signaling event leading to adherens junction uncoupling (Cohen et al, 1999;Dejana et al, 2008;McEwen et al, 2012). We recently reported that Src-activation in response to thrombin was dependent on the presence of nmMlck (Sun et al, 2011), suggesting that nmMlck could be upstream of Src-mediated tyrosine phosphorylation of the adherens junction and subsequent uncoupling. However, it is also thought that b-catenin that is dissociated from the adherens junction needs to be phosphorylated at serine residues in order to be stable in the cytoplasm (Daugherty and Gottardi, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of nmMlck in mediating both the opening of endothelial cell-cell junctions and the paracellular hyperpermeability response to proinflammatory agents (including histamine, thrombin, ROS and activated neutrophils) has been well documented (reviewed in Yuan and Rigor, 2010), the role of nmMlck in IL-1b-mediated dysfunction of the BBB has not been investigated. Because nmMlck has been shown to be involved in dissociating b-catenin from VEcadherin at the adherens junction (Sun et al, 2011), in this study, we hypothesized that nmMlck modulates IL-1b-mediated downregulation of Cldn5 and dysfunction of the BMVEC barrier in a manner that involves b-catenin activation, nuclear translocation and repression of the Cldn5 gene (Fig. 1).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In endothelial cells, this retraction is linked to endothelial permeability enhancement and vascular leakage under proinflammatory conditions. In this context, an activation of the nmMLCK has been linked to several pathophysiological conditions, such as vascular inflammation and atherosclerosis,18 acute lung injury,19 endotoxic shock,20 and severe burns 21…”
Section: Introductionmentioning
confidence: 99%
“…4 Finally, barrier function plays a role in diseases such as atherosclerosis, where poor barrier maintenance allows increased monocyte extravasation. 5 The increase in monocyte extravasation leads to macrophage colonization and the eventual buildup of plaques.…”
mentioning
confidence: 99%